Evaluation of torula yeast (Candida utilis) grown on distillery vinasse for broilers - Rodr?guez, B?rbara; Valdivi?, Manuel; Lezcano, Pedro; Herrera, Magaly (Cuban Journal of Agricultural Science, 2013)
The inclusion of torula yeast (Candida utilis) grown on distillery vinasse as alternative protein source in the diet was evaluated. Its effect was determined on the productive performance and carcass yield of broilers. Animals were housed in metallic cages (1000 birds, from 1 to 42 d of age), according to a completely randomized design. The experimental treatments consisted of a control diet (maize-soybean) and three diets including 10, 20 and 30% of vinasse torula yeast, with ten replications each. Feed consumption showed an increase (P < 0.001) with the inclusion of yeast being more marked with 20 and 30%, which influenced negatively on feed conversion, while 10% did not differ from the control and allowed the highest (P < 0.001) live weight gain (1 830 g vs. 1 803). Live weight and carcass yield with 30% torula yeast was lower (P < 0.01) than with 10%, although not differing from the control group and that of 20%. It is considered that up to 20% of vinasse torula yeast can be used in diets for broilers, as partial replacement of soybean cake meal, without affecting the productive performance and carcass yield. Key words: broilers, yeast, protein source, alternative feeds, distillery vinasse